2007
DOI: 10.1136/jramc-153-04-16
|View full text |Cite
|
Sign up to set email alerts
|

Damage Control Resuscitation

Abstract: Damage Control Resuscitation (DCR) is a novel concept that draws together a series of technical and organisational advances in combat casualty care. It is consistent with and encapsulates the established concept of damage control surgery (DCS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(54 citation statements)
references
References 5 publications
0
52
0
Order By: Relevance
“…22,33 This risk is greatly increased in wounds lying over venous sinuses, and a here very cautious approach, comprising merely gentle irrigation and attempted primary scalp closure, seems justified, with or without a CT scan. Our experience in Afghanistan suggests that patients with a single, obvious entry wound outside of the 'danger areas' and presenting with a localising response to pain (in practice, a GCS of [11][12][13] have the potential to do well with a simple decompression operation. The use of CT, combined with clinical assessment, makes it possible to determine whether decompressive surgery is appropriate and, of course, guides the exact site of the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,33 This risk is greatly increased in wounds lying over venous sinuses, and a here very cautious approach, comprising merely gentle irrigation and attempted primary scalp closure, seems justified, with or without a CT scan. Our experience in Afghanistan suggests that patients with a single, obvious entry wound outside of the 'danger areas' and presenting with a localising response to pain (in practice, a GCS of [11][12][13] have the potential to do well with a simple decompression operation. The use of CT, combined with clinical assessment, makes it possible to determine whether decompressive surgery is appropriate and, of course, guides the exact site of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The decision also takes into account the haemodynamic status and stability of the patient; neck and torso injuries may mandate either treatment-limiting decisions, or immediate surgery that takes priority over neurosurgery to control life-threatening bleeding from these areas. [11][12][13][14] In cases of penetrating head injury, clinical examination can also determine the site of proposed operation, unlike blunt trauma, where, in the absence of CT, exploratory burrholes are required. However, the decision may be complicated by the presence of both entry and exit wounds.…”
mentioning
confidence: 99%
“…More recently, conflicts in Iraq and Afghanistan have led to significant advances in health care practices, in particular damage control surgery, damage control resuscitation, massive transfusion protocols, infection control and trauma reporting systems (Aronson et al, 2006;Eastridge et al, 2006;Hodgetts et al, 2007;Wildridge et al, 2012). A citation analysis of combat casualty research identified advances in the management of massive haemorrhage as the most significant contribution to military health care and that lessons learned have been adopted into civilian trauma paradigms (Orman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Prioritising the maintenance of tissue perfusion has been instrumental in developing the UK military approach to DCR-DCS with the emphasis placed on early haemostasis, control of coagulopathy maintenance of tissue oxygenation [7,15] and limited essential surgical intervention. These concepts are now firmly established within UK military doctrine [16].…”
Section: Acute Traumatic Coagulopathymentioning
confidence: 99%